Fluoride-induced testicular and ovarian toxicity: evidence from animal studies - Seyedeh Fahimeh Talebi; Mohammad Seify; Ramji Kumar Bhandari; Hamed Shoorei; Shahram Dabiri Oskuei (Biological Research)
Abstract Fluoride (F), as a natural element found in a wide range of sources such as water and certain foods, has been proven to be beneficial in preventing dental caries, but concerns have been raised regarding its potential deleterious effects on overall health. Sodium fluoride (NaF), another form of F, has the ability to accumulate in reproductive organs and interfere with hormonal regulation and oxidative stress pathways, contributing to reproductive toxicity. While the exact mechanisms of F-induced reproductive toxicity are not fully understood, this review aims to elucidate the mechanisms involved in testicular and ovarian injury. In males, F exposure at different doses has been associated with reduced testis weight, reduced sperm quality in terms of count, motility, and viability, as well as abnormal sperm morphology and disruption of seminiferous tubules by altering hormone levels (especially testosterone), impairing spermatogenesis, and inducing oxidative stress and zinc deficiency. Similarly, administration of F can impact female reproductive health by affecting ovarian function, hormone levels, oocyte quality, and the regularity of the estrous cycle. However, the impact of F exposure on LH, FSH, and GnRH levels is controversial between males and females. In both males and females, F exerts its adverse effects by triggering apoptosis, autophagy, inflammation, mitochondrial dysfunction, reduction in ATP synthesis, and modulation of important genes involved in steroidogenesis. Furthermore, genetic susceptibility and individual variations in F metabolism may contribute to different responses to fluoride exposure.